Observation of Brillouin scattering in a high-index doped silica chip waveguide - M. Zerbib; V.T. Hoang; J.C. Beugnot; K.P. Huy; B. Little; S.T. Chu; D.J. Moss; R. Morandotti; B. Wetzel; T. Sylvestre (Results in Physics, 2023)
We report the observation of Brillouin backscattering in a 50-cm long spiral high-index doped silica chip waveguide and measured a Brillouin frequency shift of 16 GHz which is in very good agreement with theoretical predictions and numerical simulations based on the elastodynamics equation. © 2023.